Topp-Leone Fréchet Distribution with Theory and Application - Sapkota, Laxmi Prasad (Janapriya Journal of Interdisciplinary Studies, 2021)
We have defined a new distribution as a generalization of Frechet distribution called the Topp-Leone Frechet distribution. Some properties and characteristics of the proposed distribution are presented. The hazard rate function can have the shape of the reverse-j, right-skewed and unimodal. The parameters of the proposed model are estimated by employing the maximum likelihood estimation (MLE) method and asymptotic confidence intervals for MLEs are also provided. R software is used for computational purpose. The application of the Topp-Leone Frechet distribution is presented by considering a real dataset and found that the proposed model provided a good fit as compared with some competing models